Genotype differences in the metabolism of proline and polyamines under moderate drought in tomato plants. (22nd April 2014) - Montesinos‐Pereira, D.; Barrameda‐Medina, Y.; Romero, L.; Ruiz, J.M.; Sánchez‐Rodríguez, E.; Sparks, J.
Abstract Water stress is one of the most important factors limiting the growth and productivity of crops. The implication of compatible osmolytes such as proline and polyamines in osmotic adjustment has been widely described in numerous plants species under stress conditions. In the present study, we investigated the response of five cherry tomato cultivars (Solanum lycopersicum L.) subjected to moderate water stress in order to shed light on the involvement of proline and polyamine metabolism in the mechanisms of tolerance to moderate water stress. Our results indicate that the most water stress‐resistant cultivar (Zarina) had increased degradation of proline associated with increased polyamine synthesis, with a higher concentration of spermidine and spermine under stress conditions. In contrast, Josefina, the cultivar most sensitive to water stress, showed a proline accumulation associated with increased synthesis after being subjected to stress. In turn, in this cultivar, no rise in polyamine synthesis was detected. Therefore, all the data appear to indicate that polyamine metabolism is more involved in the tolerance response to moderate water stress.